Successful Endoscopic Management of Obstructive Jaundice in Von Hippel-Lindau Disease Caused by Multiple Pancreatic Serous Cystadenomas’ Extrinsic Compression - A Case Report - MD, Hunter Benvenuti; MD, Mandeep Singh; MD, Amir H Fathi; FACS, (Archives of Clinical and Medical Case Reports, 2020)
Serous cystadenomas of the pancreas are a common entity in patients with von Hippel-Lindau (vHL) disease. However, to date, only thirteen cases of pancreatic cystic lesions causing obstructive jaundice in vHL patients have been reported in the literature, and these were the result of distal CBD stricture. In this study, we present a rare first case report of multiple large pancreatic serous cystadenomas causing obstructive jaundice via extrinsic compression of the mid CBD in a 27-year-old female with vHL. Biliary decompression has been successfully achieved with ERCP and stent placement, with serial stent exchanges every 2 months. Given the patient’s young age and the morbidity associated with total pancreatectomy, we have elected to pursue a more conservative approach to her biliary obstruction via serial stent exchanges until they are no longer successful at achieving decompression, at which point we will proceed with surgical intervention such as biliary bypass or total pancreatectomy.